The effect of regulatory scrutiny asymmetric cost pass-through in power wholesale and its end - Frieder Mokinski; Nikolas Wölfing (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
We find an asymmetric pass-through of European Emission Allowance (EUA) prices to wholesale electricity prices in Germany and show that this asymmetry has disappeared in response to a report on investigations by the competition authority. The asymmetric pricing pattern, however, was not detected at the time of the report, nor had it been part of the investigations. Our results therefore provide evidence of the deterring effect of regulatory monitoring on firms which exhibit non-competitive pricing behavior. We do not find any asymmetric pass-through of EUA prices in recent years. Several robustness checks support our results.
urn:nbn:de:bsz:180-madoc-345994
Keywords: L4; L94; Q41; Q52; 330; asymmetric price adjustment; regulatory monitoring; wholesale electricity markets; emission trading